Impacto da adição do hidróxido de cálcio em adesivos autocondicionantes experimentais: influência no grau de conversão e PH - Amorim, Débora Michelle Gonçalves de (2017)
Purpose: To evaluate the impact of the addition of calcium hydroxide - Ca (OH) 2 on the neutralization of pH and degree of conversion of experimental self - etching adhesives. Methods: Four adhesives were formulated in two flasks: Bottle A, containing UDMA, HEMA, GDMA-P, TPO, DH and solvent; Bottle B: composed of UDMA, HEMA, TPO, DH. The solvents used were ethanol and water (1: 1). The concentration of Ca (OH) 2, added to flask B, in the mass fractions of 0% (control), 1%, 2% and 4% was evaluated, and the adhesives were divided into four groups (A + B0, A + B1, A + B2, A + B4). Equal volumes of bottles A and B of each adhesive were mixed and ~ 5 μ of this mixture was inserted into silicone molds to make the disks. Before polymerization of the adhesive the pH of the adhesive was measured through a pH meter. After the photoactivation, the disks (n = 5) were immersed in distilled water, and pH readings of the eluate were performed for 72h. To evaluate the degree of conversion, five samples of each adhesive were submitted to the FTIR, with attenuated total reflectance (ATR) device, before and after the photoactivation of the samples. For the photoactivation procedures, a 3rd generation LED light source - Bluephase G2 was used. The data were statistically evaluated by ANOVA 1 factor (degree of conversion and pH of the adhesive) and 2 factors (pH of the eluate) and Tukey's post-test (p <0.05). Results: No statistically significant difference was found between the experimental adhesives tested in the conversion test. The pH of the experimental adhesives tested were all statistically different from each other. The pH of the eluate was neutralized in the A + B2 and A + B4 groups after the immersion period. Conclusion: the degree of conversion was not affected by the incorporation of calcium hydroxide. The pH of the adhesive and the eluate was neutralized with the addition of calcium hydroxide. Keywords: Calcium Hydroxide, Spectroscopy, Fourier Transform Infrared, Dentin-Bonding Agents.